Jangha of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The jangha (wall) of the Kaner-ki-Putli Temple has central offsets flanked by projections and recesses. The niches of the central offsets on all three sides of the garbhagriha (sanctum sanctorum) are presently empty. These niches may have originally been adorned with depictions of deities. The remaining projected and recessed sections are intricately carved with depictions of minor deities, including dikapalas (deities of cardinal directions), Shaiva ascetics, and female figures.